India's Rise to Power in the Twentieth Century and Beyond - Gordon, Sandy (London Macmillan, 1995)
Examines the economic and technological basis for India's rise to power and the political factors that will shape the country in the future. The book juxtaposes the advances that India has made
Include Appendix, Bibliography, Index and Illustrations
Keywords: India -- Politics and government -- Political Science